Analysis of the Legal Implications of TikTok's Exoneration Clause on Platform Liability Under Indonesian Consumer Protection Law - Ridwan Tobing; Zuhdi Hasibuan (Islamic Circle, 2025)
The development of digital technology raises new legal issues, especially related to the provisions on the limitation of platform liability (exoneration) in consumer protection efforts. Consumers often encounter obstacles in seeking justice because platforms generally claim to only act as intermediaries, thus denying responsibility for problems arising between third parties. TikTok's limitations on liability in its legal relationship with consumers need to be studied further because they are related to the protection of consumer rights in the digital era. This study analyzes the exoneration clause in TikTok's terms and conditions from the perspective of Consumer Protection Law in Indonesia. The focus of the study is on the exoneration clause set by TikTok, which limits users' rights to obtain compensation for certain losses. Based on the results of the analysis, this clause has the potential to conflict with Article 18 of Law No. 8 of 1999 concerning Consumer Protection because it eliminates the balance of rights and obligations between TikTok and users. The limitation of liability that only reaches the total payment in the last 12 months is considered unbalanced and has the potential to harm users. Through this study, it is recommended that the clause be changed so that it can be in line with the principles of justice and applicable regulations, then can provide protection for consumers and avoid legal risks in the future.